EQOFIX: a combined economic and quality-of-life study of hemophilia B treatments in France - Polack, Benoît; Calvez, Thierry; Chambost, Hervé; Rothschild, Chantal; Goudemand, Jenny; Claeyssens, Ségolène; Borel-Derlon, Annie; Bardoulat, Isabelle; Maurel, Frédérique; Woronoff-Lemsi, Marie-Christine (Transfusion, 2015)
BACKGROUND EQOFIX is a medicoeconomic study that analyzed the health‐related quality of life (HRQoL) and costs of care of the moderate and severe forms of hemophilia B, treated on demand or by prophylaxis with either plasma‐derived Factor IX (pdFIX) or recombinant FIX (rFIX). STUDY DESIGN AND METHODS The primary objectives were evaluations of the impact of hemophilia B on HRQoL and of the costs associated with its management. The secondary objectives were evaluations of the clinical efficacy and costs of care of pdFIX and rFIX. In this observational study we included and followed for 1 year severe and moderate hemophilia B patients without inhibitor. HRQoL was evaluated through generic and disease‐specific questionnaires. Information on the health resources consumed was collected every 3 months. RESULTS The EQOFIX cohort was composed of 155 patients, including 51 children and 104 adults, with 114 having severe disease and 41 having moderate disease. The regimens were prophylactic for 61 and on demand for 94. Altogether, 78 were treated with rFIX and 77 with pdFIX. There was no difference in the QoL between the pdFIX and rFIX treatments. The extra cost of prophylaxis was €22,605 per bleeding event prevented. The consumption of FIX was 1.4‐fold higher for the patients treated with rFIX than for the patients treated with pdFIX. CONCLUSION Our findings in a cohort composed of 25% of the French population of moderate and severe hemophilia B patients show, with similar clinical and HRQoL results, that treatment with rFIX is more expensive than treatment with pdFIX.